The Role of cAMP-PKA Pathway in Lactate-Induced Intramuscular Triglyceride Accumulation and Mitochondria Content Increase in Mice - Chen, Siyu; Zhou, Lei; Sun, Jingquan; Qu, Yaqian; Chen, Min (Frontiers in Physiology, 2021)
The glycolytic product of exercise, lactate, has long been recognized to promote lipid accumulation by activation of G-protein-coupled receptor 81 (GPR81) and inhibition of the cAMP-PKA pathway in adipose tissue. Whether lactate causes a similar process in skeletal muscle is unclear. Lactate might also improve mitochondria content in skeletal muscle, however, the mechanism is not clarified either. In this study, using intramuscular injection of lactate to the gastrocnemius and intraperitoneal injection of forskolin (activator of cAMP-PKA pathway), we identified the role of the cAMP-PKA pathway in lactate-induced intramuscular triglyceride accumulation and mitochondrial content increase. The intramuscular triglyceride level in the gastrocnemius increased after five weeks of lactate injection (P < 0.05), and this effect was blocked by forskolin injection (P < 0.05). Corresponding expression level changes of GPR81, P-PKA/PKA, P-CREB/CREB and proteins related to lipid metabolism suggest that lactate could induce intramuscular triglyceride accumulation partly through the inhibition of the cAMP-PKA pathway. Meanwhile, the intramuscular expression of citrate synthase (CS) and the activity of CS increased after five weeks of lactate injection (P < 0.05), but the change of CS expression was not blocked by forskolin injection, suggesting other mechanisms might exist. Consequently, exploration for other potential mechanisms that might contribute to the lactate-induced mitochondria content increase was conducted. We found an increase in the contents of lactate-related metabolites in skeletal muscle mitochondria after acute lactate injection (the P-value of each analysis is less than 0.05). LHDA was also validated to exist in mitochondria in this study. These results provide a possibility for metabolism-related mechanisms of lactate-induced mitochondria content increase. Future study is needed to validate this hypothesis. In conclusion, lactate-induced intramuscular triglyceride accumulation is achieved by inhibition of lipolysis, and this process is regulated by the cAMP-PKA pathway. Promoted lipogenesis also contributes to lactate-induced triglyceride accumulation, and this process might also be regulated by the cAMP-PKA pathway. Lactate injection might increase mitochondria content and cAMP-PKA pathway might have a limited contribution, while other metabolism-related mechanisms might play a prominent role.